Dragon fruit (Hylocereus spp.) as a potential crop for nutraceutical properties, livelihood enhancement and climate change mitigation - Mangalambika Balaji; Utpal Das; Rahul Vashishth (Cogent Food & Agriculture)
Dragon fruit, scientifically known as Hylocereus spp. has emerged as a promising crop addressing climate change and rural poverty. Its ability to withstand extreme environmental conditions, including drought and high temperatures, makes it suitable for arid and semi-arid regions. Low water and resource requirements enhance its sustainability, making it optimal for resource-constrained agricultural systems. This study highlights dragon fruit’s economic significance and commercial viability, emphasizing its role in developing functional foods, nutraceuticals, and climate-resilient agricultural practices. Integration into traditional farming systems presents value addition opportunities, contributing to both economic and environmental sustainability. Dragon fruit cultivation offers substantial benefits for smallholder farmers, ensuring profitability despite minimal inputs. Its high market value, coupled with rich bioactive compounds-including vitamins, minerals, and nutraceuticals-positions it as a valuable health benefits. These attributes show that dragon fruit holds considerable promise for future agricultural systems, aligning with global efforts toward sustainable food production and enhanced rural livelihoods.